2017
DOI: 10.1111/bjep.12206
|View full text |Cite
|
Sign up to set email alerts
|

School readiness in children with special educational needs and disabilities: Psychometric findings from a new screening tool, the Brief Early Skills, and Support Index

Abstract: The BESSI appears to be a useful tool in screening children for more detailed assessment of SEND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The positive predictive value was, however, much lower, with only around 36% of children not reaching a good level of development requiring support for SEN. Such findings are broadly in line with Hughes et al (2018), who examined whether the Brief Early Skills and Support Index could identify children with SEN. Thus, whilst both evaluations successfully detect most children who will require SEN support, they do appear to overidentify the number of children at risk.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The positive predictive value was, however, much lower, with only around 36% of children not reaching a good level of development requiring support for SEN. Such findings are broadly in line with Hughes et al (2018), who examined whether the Brief Early Skills and Support Index could identify children with SEN. Thus, whilst both evaluations successfully detect most children who will require SEN support, they do appear to overidentify the number of children at risk.…”
Section: Discussionsupporting
confidence: 84%
“…It would, however, be beneficial to examine whether school readiness measures can identify children with SEN more generally (as opposed to specific developmental disorders or difficulties). To the best of our knowledge, only one study to date has examined this thus far (Hughes et al, 2018). In this study, it was found that a teacher-rated evaluation of school readiness (the Brief Early Skills and Support Index), which assesses a variety of abilities at school entry such as 'daily living skills' and 'language and cognition' could correctly classify whether children had SEN.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The BESSI is a validated questionnaire developed by Hughes et al (2015) for teachers to determine how well a child is transitioning into school. The questionnaire has good test-retest reliability, established longitudinal measurement invariance (Hughes, White, Foley, & Devine, 2018) and is sensitive to special educational needs status (Hughes, Foley, White, & Devine, 2017). Alongside three child-related subscales (behavioural adjustment, language and cognition, and daily living skills), the questionnaire includes a family support subscale, indicating the degree to which children receive support for their education from their home/family life.…”
Section: Teacher-rated School Readinessmentioning
confidence: 99%
“…Instrumental learning, especially in regards to difficulties in reading and literacy, is one of the main concerns of research on the psychology of education (Lloyd et al, 2009;Alanazi, 2017;Alenizi, 2019;Auphan et al, 2019;Hughes et al, 2018). Numerous programs for improving reading and/or reading difficulty prevention have emerged from research on reading and literacy from the perspective of the psychology of education, and their impact on improving children's learning has been analyzed (Vellutino and Scanlon, 2002;Papadopoulos et al, 2004;Hatcher et al, 2006).…”
mentioning
confidence: 99%